PREFERENSI MAHASISWA MENABUNG DI PERBANKAN SYARIAH : STUDI PADA MAHASISWA PERGURUAN TINGGI DKI JAKARTA - Farah Dibah; Suryani Suryani; Lili Puspita Sari (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
The development of Islamic banking in Indonesia is growing rapidly, supported by the great potential in the DKI Jakarta area. After the merger of Islamic banks in 2021 caused student awareness of Islamic financial transactions to increase. This study aims to examine the effect of service quality, brand image, and knowledge on student preferences for saving in Islamic banking. Sampling through purposive sampling method which was tested on 100 respondents. The data collection instrument used a questionnaire with a Likert scale. The analytical technique used to determine the magnitude of this effect is multiple linear regression assisted by the SPSS version 25 program. The test results show that (1) service quality has a significant effect on student preferences for saving in Islamic banking, (2) brand image has no significant effect on student savings preferences. in Islamic banking, (3) knowledge has a significant effect on student preferences for saving in Islamic banking, (4) service quality, brand image, and knowledge have a significant effect on student preferences for saving in Islamic banking.